A Possible Association Between Zika Virus Infection and CDK5RAP2 Mutation - Candelo, Estephania; Sanz, Ana Maria; Ramirez-Montaño, Diana; Diaz-Ordoñez, Lorena; Granados, Ana Maria; Rosso, Fernando; Nevado, Julian; Lapunzina, Pablo; Pachajoa, Harry (Frontiers in Genetics, 2021)
Introduction Flaviviridae family belongs to the Spondweni serocomplex, which is mainly transmitted by vectors from the Aedes genus. Zika virus (ZIKV) is part of this genus. It was initially reported in Brazil in December 2014 as an unknown acute generalized exanthematous disease and was subsequently identified as ZIKV infection. ZIKV became widespread all over Brazil and was linked with potential cases of microcephaly. Case report We report a case of a 28-year-old Colombian woman, who came to the Obstetric Department with an assumed conglomerate of fetal abnormalities detected via ultrasonography, which was performed at 29.5 weeks of gestation. The patient presented with multiple abnormalities, which range from a suggested Arnold–Chiari malformation, compromising the lateral and third ventricles, liver calcifications, bilateral pyelocalic dilatations, other brain anomalies, and microcephaly. At 12 weeks of gestation, the vertical transmission of ZIKV was suspected. At 38.6 weeks of gestation, the newborn was delivered, with the weight in the 10th percentile (3,180 g), height in the 10th percentile (48 cm), and cephalic circumference under the 2nd percentile (31 cm). Due to the physical findings, brain magnetic resonance imaging (MRI) was performed, revealing a small and deviated brain stem, narrowing of the posterior fossa, a giant posterior fossa cyst with ventricular dilatation, a severe cortical and white matter thinning, cerebellar vermis with hypoplasia, and superior and lateral displacement of the cerebellum. In addition, hydrocephalus was displayed by the axial sequence, and the cerebral cortex was also compromised with lissencephaly. Schizencephaly was found with left frontal open-lip, and no intracranial calcifications were found. Two novel heterozygous nonsense mutations were identified using whole-exome sequencing, and both are located in exon 8 under the affection of ZIKV congenital syndrome (CZS) that produced a premature stop codon resulting in the truncation of the cyclin-dependent kinase 5 regulatory subunit-associated protein 2 (CDK5RAP2) protein. Conclusion We used molecular and microbiological assessments to report the initial case of vertically transmitted ZIKV infection with congenital syndrome associated with a neurological syndrome, where a mutation in the CDK5RAP2 gene was also identified. The CDK5RAP2 gene encodes a pericentriolar protein that intervenes in microtubule nucleation and centriole attachment. Diallelic mutation has previously been associated with primary microcephaly.